2012
DOI: 10.2460/javma.241.3.331
|View full text |Cite
|
Sign up to set email alerts
|

Enteropathogens identified in cats entering a Florida animal shelter with normal feces or diarrhea

Abstract: In the present study, cats entered the shelter with a variety of enteropathogens, many of which are pathogenic or zoonotic. Most infections were not associated with diarrhea or any specific risk factors such as signalment, source, or body condition, making it difficult to predict which cats were most likely to be infected. It is not possible to test all shelter cats for all possible infections, so practical guidelines should be developed to treat routinely for the most common and important enteropathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
84
4
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(103 citation statements)
references
References 46 publications
13
84
4
2
Order By: Relevance
“…Table 1). The lack of defined clinical symptoms in cats shedding one of the viruses supports prior studies reporting frequent enteric viral infections in healthy animals (Sabshin et al, 2012; Shan et al, 2011) and humans (Ayukekbong et al, 2011; Kapusinszky et al, 2012; Witsø et al, 2006). In order to determine whether these feline viruses may cause disease in a subset of animals (e.g.…”
Section: Discussionsupporting
confidence: 80%
“…Table 1). The lack of defined clinical symptoms in cats shedding one of the viruses supports prior studies reporting frequent enteric viral infections in healthy animals (Sabshin et al, 2012; Shan et al, 2011) and humans (Ayukekbong et al, 2011; Kapusinszky et al, 2012; Witsø et al, 2006). In order to determine whether these feline viruses may cause disease in a subset of animals (e.g.…”
Section: Discussionsupporting
confidence: 80%
“…We were also able to use the differential pan-Salmonella FRET-PCR to detect Salmonella in dog and cat feces from apparently healthy animals. Although we did not culture the feces from the dogs and cats and were therefore unable to precisely determine the sensitivity and specificity of the test when performed directly on fecal samples, our findings are comparable with other studies using PCR which found Salmonella in 6% and 2% of dogs [24] and cats [25] with normal feces, respectively. Further studies are underway in our laboratory to determine the sensitivity of the PCR in detecting DNA of Salmonella directly in tissue, fecal and environmental samples.…”
Section: Discussionsupporting
confidence: 74%
“…Vertical transmission has not been demonstrated (Foley et al, 1997). Persistently infected, asymptomatic carriers spread FCoV since most of these cats shed the virus for a period of months or years, either continuously or transiently (Foley et al, 1997;Cave et al, 2004;Dye et al, 2008;Kipar et al, 2010;Sabshin et al, 2012).…”
Section: Introductionmentioning
confidence: 99%